Políticas e formação de professores em Educação Física - Rodrigo Roncato Marques Anes (EccoS – Revista Científica)
In this paper are discussed the policies for training in Physical Education, taking as its starting point an analysis about the political restructuring that resulted in curricular reform movement from the 1990s. We believe that such policies and their consequences determined directly reorganizing the educational perspective in Brazil, including higher education, directing them by the principles laid down and prepared by multilateral organizations. In the case of training in physical education is clear that these guidelines, to some extent, were directly responsible for the establishment of an area of crisis characterized by contradiction, conflict and fragmentation, and for that reason needs to be better understood and reflected.